Aircraft design optimisation conceptual evaluation of a three-lifting surface turbo-fan airliner - Basto Nunes, J. M. (Cranfield University, 1995)
Today's high competitiveness in the airline industry urges for the development of even more efficient transport aircraft. In many cases lower operating costs are the key to survival. Although the introduction of emerging advanced technologies has shown improvements both in safety levels and performance, with the associated reductions in costs, the search for more economical aircraft must also take into consideration changes in current design practice. The study of novel configurations is a contribution to this view. In this research project, advantage was taken from multidisciplinary synergism to design and optimise conventional and three-surface configuration commercial aircraft, to satisfy the same mission and operational requirements. An integrated conceptual design synthesis approach was employed where typical aeronautical disciplines, as well their complex inter-relations, were taken intoaccount. All these considerations, together with both cruise and field performance, and static stability and control requirements, resulted in different baseline configurations of the two concepts, although sharing the same fuselage and the same technology standard, but with different Maximum Take-off Weights (MTOW), lifting surfaces, turbo-fan engine sizes, and economics. After coupling the design synthesis program to a gradient based numerical minimization routine, optimisation of these designs was performed for minimum Direct Operating Costs (DOC) and minimum MTOW, and their performance and economics were compared on an equal basis. Trade-off studies were conducted on all aircraft for 1000 through 3000 NM design mission ranges while keeping the same fuselage size, lifting surface planform shapes and same static longitudinal stability margin (inherently stable designs), as obtained for the respective datum designs (Range = 1250 NM). Thus, using the same comprehensive design tool, built on the same primary assumptions, and using the same analytical methods and principles which include many real life considerations, a systematic and conýistent study of both design concepts was conducted. The potential merits of a realistic three-surface transport design were clearly established, when comparison was made with an equivalent mission conventional twin turbo-fan airliner. Within the usual limitations of any initial conceptual design study, it appears that the concept of the three-lifting surface transport can effectively improve in terms of performance and direct operating costs, when compared to conventional aircraft designed for the same operational environment and mission profiles, and may show a promising future.